P161Two cardioprotective regimens of chronic intermittent hypoxia differ in activation of antioxidant systems. (15th July 2014) - Kasparova, D; Neckar, J; Kolar, F; Novotny, J; Novakova, O; Zurmanova, J
Abstract: Purpose: We have shown that long-term adaptation to intermittent normobaric hypoxia (INH) or to intermittent hypobaric hypoxia (IHH) for 8 h per day improves myocardial tolerance to acute ischemia-reperfusion injury. Reactive oxygen species formed during hypoxic exposures play an important role in the induction of protective cardiac phenotype. Methods: Adult male Wistar rats were exposed to chronic intermittent hypoxia for 8 h per day. First group was kept in normobaric chamber (INH, 10% O2) and second one in hypobaric chamber (IHH, 7000m, PO2 = 8, 5kPa). We aimed to analyse, by Real Time PCR, the mRNA expression of several components of antioxidant systems and main hypoxic transcription factors HIF1α and HIF2α together with their regulating hydroxylases in the left ventricle of rats adapted to either INH or IHH. Results: The comparison of these hypoxic regimes showed that cytosolic and mitochondrial superoxide dismutases, producing hydrogen peroxide, were elevated in INH but depressed in IHH when compared with normoxic controls. Catalase, which subsequently eliminates hydrogen peroxide, was not affected in INH but it decreased in IHH. Its function was substituted by the increased expression of glutathion peroxidase 4 (by 23%) and peroxiredoxins (by 25%) in INH, while in IHH these enzymes either decreased or remained unchanged, respectively. Aconitase 1 and hemoxygenase 1 were the only elevated antioxidants in IHH (by 45% and 23%, respectively). The mRNA of HIF1, HIF2 and asparaginyl hydroxylase was increased (by 18%, 109% and 79%) respectively, in INH only. Conclusions: We conclude that the two protective regimens of intermittent hypoxia differ in the effect on the expression of myocardial antioxidant systems. While INH stimulated the expression of HIF1α, HIF2α and major antioxidant enzymes, the antioxidant defence in more severe IHH regimen was supported only by iron-dependent systems. This work was supported by the Charles University Grant Agency (628412) and the Czech Science Foundation (P303/12/1162).